2013
DOI: 10.1007/s11248-013-9727-2
|View full text |Cite
|
Sign up to set email alerts
|

A new method for producing transgenic birds via direct in vivo transfection of primordial germ cells

Abstract: Traditional methods of avian transgenesis involve complex manipulations involving either retroviral infection of blastoderms or the ex vivo manipulation of primordial germ cells (PGCs) followed by injection of the cells back into a recipient embryo. Unlike in mammalian systems, avian embryonic PGCs undergo a migration through the vasculature on their path to the gonad where they become the sperm or ova producing cells. In a development which simplifies the procedure of creating transgenic chickens we have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 19 publications
2
84
0
3
Order By: Relevance
“…To find the most efficient transposon, we compared the transfection efficiency of PGCs across four transposons by screening the GFP-positive gonads. All of these transposons were highly efficient, and no significant difference was observed in the proportion of GFP-positive gonads, which also suggests that all four of these transposons are applicable in chicken transgenesis and that their efficiency is consistent with that previously reported (Tyack et al, 2013). We also found that combining PEI with a high dose (100 ng) of plasmid can generate a high proportion of GFP-positive gonads, while combining PEI with a low dose (20 or 50 ng) of plasmid can generate a low proportion of GFP-positive gonads, but with a limited increase in the hatching rates and viability of embryos, which indicates that the hatching rates and viability of embryos may be affected mainly by the physical injury of the injection, not the dose of plasmid or transfection reagent.…”
Section: Discusssupporting
confidence: 87%
See 2 more Smart Citations
“…To find the most efficient transposon, we compared the transfection efficiency of PGCs across four transposons by screening the GFP-positive gonads. All of these transposons were highly efficient, and no significant difference was observed in the proportion of GFP-positive gonads, which also suggests that all four of these transposons are applicable in chicken transgenesis and that their efficiency is consistent with that previously reported (Tyack et al, 2013). We also found that combining PEI with a high dose (100 ng) of plasmid can generate a high proportion of GFP-positive gonads, while combining PEI with a low dose (20 or 50 ng) of plasmid can generate a low proportion of GFP-positive gonads, but with a limited increase in the hatching rates and viability of embryos, which indicates that the hatching rates and viability of embryos may be affected mainly by the physical injury of the injection, not the dose of plasmid or transfection reagent.…”
Section: Discusssupporting
confidence: 87%
“…10;2016 Although the transfection of PGCs can be achieved by injecting plasmid DNA and liposome complexes into the bloodstream of stage HH 14 embryos (Watanabe et al, 1994), this method is inefficient and unstable without a transposon medium. Combining transposons with transfection reagents has been shown to be effective for chimera production and germline transgenesis by direct injection into the vasculature of developing chick embryos or stage X embryos (Jordan et al, 2014;Tyack et al, 2013). The combination of Tol2 transposon with Lipofectamine 2000 has been confirmed to transfect the PGCs efficiently in vivo by direct injection into the vasculature of developing chick embryos and to generate stable germ-line transgenic male chickens who passed the transgene onto their offspring (Tyack et al, 2013).…”
Section: Discussmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers can therefore remove PGCs, edit them in the lab and then return them to the developing bird. The CSIRO team has even developed a method to insert CRISPR components directly into the bloodstream so that they can edit PGCs there 4 . The researchers also plan to produce chickens with components required for CRISPR integrated directly into their genomes -what they call CRISPi chickens.…”
Section: A K I N G D R U G Smentioning
confidence: 99%
“…The use of this type of cells in selection and biotechnological programs opens wide opportunities for directed genome modification and the reconstruction of valuable breeds and lines preserved in cryobank conditions [6][7][8][9][10][11][12]. Peculiarities of biology of agricultural poultry allow us to consider PGC as a promising genetic material.…”
Section: Introductionmentioning
confidence: 99%